Phosphonanaloga von Aminosäuren und Peptiden: Synthese der Phosphonanaloga von Depsipeptiden mittels der Passerini-Reaktion. - Janusz Rachoń (CHIMIA)
Synthesis of phosphorous analogues of tri- and tetra-depsipeptides 4 involving the Passerini reaction of diethylisocyanmethylphosphonate 3 with carbonyl compounds 2 and N-protected glycine 1 is reported.